Cascade annulation reaction (CAR): highly diastereoselective synthesis of pyranopyrazole scaffolds. Issue 32 (19th May 2020) - Bakthadoss, Manickam; Surendar, Manickam
Abstract : An unprecedented domino protocol for the novel synthesis of highly diverse and functionalized tetrahydro pyranopyrazole scaffolds using chalcone epoxide has been reported. Abstract : An unprecedented domino protocol for the novel synthesis of highly diverse and functionalized tetrahydro pyranopyrazole scaffolds using chalcone epoxide has been reported for the first time. This synthetic protocol generates three consecutive stereogenic centres in a highly diastereoselective manner with the formation of vicinal diol and a quaternary carbon centre. A wide range of substrates were utilized for the scope of this methodology and provided very good yields of pyranopyrazoles. The pyranopyrazoles were also transformed into densely functionalized tetrasubstituted olefins.